Use of human cadavers in teaching of human anatomy in brazilian medical faculties - Isabela de Sousa Leal Lopes; Bruna de Alcobaça Castelo Branco Teixeira; Pedro Olímpio Barros Cavalcante Cortez; Guilherme Rodrigues da Silva; Antônio Isidora de Sousa Neto; Noelia Maria de Sousa Leal (Acta Scientiarum. Biological Sciences, 2017)
The Human Anatomy is the study of human body structure and it has been related to the use of cadavers through the history. The aim of this research was to investigate the use of human cadavers in practical classes of human anatomy in Brazilian medical schools, and it was also made the identification of alternative methodologies and new technologies applied to the teaching of Anatomy. The research was conducted at the Faculdade Integral Diferencial from January to December of 2015. The population studied was composed by professors responsible for the Human Anatomy sector of the Brazilian medical faculties. It was addressed all the 242 medical colleges of the Brazil. It was obtained 81 answers. 96% of respondents reported make use of human corpses in its practical lessons of anatomy. It can be observed that 42% of the surveyed medical schools make use of only formaldehyde. 81% of faculties reported to face some difficulties to acquire human cadavers. 84% of medical schools make use of artificial models. 46% of faculties make use of diagnostic images. It can be concluded that human bodies, artificial models and new technologies are widely used in practical classes of anatomy in Brazil, since there is a difficulty to obtain cadavers.